LAPORAN KASUS:DICEPHALUS DIPUS TETRABRACHIUSDARI MALANG - Dradjat, Respati Suryanto (Jurnal Kedokteran Brawijaya, 2007)
Dicephalus Dipus Tetrabrachius is an extremely rare  form of conjoined twinning in which the infant has  four arms, two legs, one trunk, but two heads. The case that was born in Malang was girls had four arms that two of the arms had fused at the mid line. The case was delivered by caesareansection, due to pre-eclampsia and prolonged labor.Prior antenatal care was never done; the babies were born without any suspicion of conjoined twin. According to literature almost sixty percent of conjoined twins are either stillborn or lost in uterus, and 35% of twins that survive die within the first 24 hours. Antenatal diagnosis by ultrasound is possible in modern day obstetrics. The babies were born on Oct. 21st, 2006. The treatment planning were determined by degree of fusion and extent of joining of fetal organs. Surgicalseparation was not possible; the surgical correction is removal of fused arms in the near future, as an alternative plan for improving quality of life. Unfortunately the conjoined twin died 1 week before 6 month old. Key words:Conjoined twin, dicephalus, prognosis, treatment